Handbook of Parathyroid Diseases A Case-Based Practical Guide - Khan, MD, Aliya A.; Clark, Orlo H. (Springer New York : Imprint: Springer, 2012)
The Handbook of Parathyroid Diseases presents a comprehensive and concise overview of our current knowledge in the area of parathyroid function, hormone regulation and disease states. The Handbook educates the reader using a case-based approach presenting current evidence in the field. The material is presented in an easy to read and understandable language and uses a plethora of tables and text boxes where possible. Complex concepts are conveyed in simple and clear language. Leading international experts contribute to this state of the art book providing a true depth of knowledge and practicality.